An improved method for achieving chronic blood pressure reduction following bilateral adrenal demedullation of young hypertensive rats - Mohd Noor, Noriah; Abdullah, Aszrin; Abdul Razak, Tariq (2011)
Adrenal demedullation in young adult, spontaneously hypertensive rats( SHRs) results in blood pressure reduction. However, inconsistent postoperative care of demedullated animals may results in indifferent study findings. The study aims to determine whether an improved method could prevent elevation of blood pressure in young adult SHRs. Fourteen young male and female SHRs weighing 200-270g and 150-170g, respectively were studied. Six were sham-operated age-matched controls and 8 adrenal demedullated.The bilateral adrenal demedullation surgery was adapted from Griffith and Farris (1942) and Borkowski and Quinn (1983). The rats were given distilled water postoperatively. All postoperative SHRs were given supplemental heat until they regained consciousness and were able to maintain normal posture. Indirect systolic blood pressure (SBP) was measured by tail cuff method at 1 week and 2 weeks postoperatively. The mean preoperative SBP in control and tested group were 168.78 + 5.80 and 163.15 + 16.26 mmHg respectively. The mean postoperative SBP at 1 week were 170.00 + 9.61 and 128.31 + 19.36 mmHg respectively (p values of 0.753 and 0.012, Wilcoxon Signed Ranks Test- compared to preoperative mean values). The mean postoperative SBP at 2 weeks were 170.50 + 6.22 and 129.00 + 13.34 mmHg respectively (p values of 0.92 and 0.028). Comparison between adrenal demedullated groups and control group SBP show significant SBP difference, at 1 week (p values of 0.005 Mann-Whitney U) and 2 weeks respectively, (p values 0.004). Ad libitum distilled water supplementation and an improved postoperative care allows a sustained normal mean SBP following demedullation in SHRs.